THE ANALYSIS OF JOB ENRICHMENT AMONG EMPLOYEE IN BADAN PENDAPATAN DAERAH KOTA MANADO - Rumerung, Yemima K.; Lapian, Joyce; Tumbuan, Willem J.F.A (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: Job enrichment is a way to motivate employees by giving them increased responsibility and variety in their job. The objective of job enrichment is to provide opportunities for achievement, recognition, advancement, responsibility, and growth. The aim of this study is to know what factors that influence job enrichment among the employees in Badan Pendapatan Daerah Kota Manado. In order to achieve this objective, the researcher got information from 15 informants, using a qualitative study which is an in-depth interview and uses purposive sampling. The results showed that job enrichment in Badan Pendapatan Daerah Kota Manado has been running well and effectively to influence the employees to work better, job enrichment gives a positive impact to employees, employees get the opportunity to learn a new skill and improve creativity. Recommendation of this research to the institution, this research may help them to always keep improving employee performance by doing good job enrichment.Â Keywords: Job Encrichment, Human Resources